The Effect Of Customer Service Quality on Customer Satisfaction at PT Bank Central Asia Thamrin Central Jakarta Branch - Aprilia Pramesty, Nanda; I Wayan Ray, Raymundus; Wijayanto, Hendra; Pangestu, Angella Rosha (Zona Law And Public Administration Indonesia, 2024)
The purpose of this study is to determine the effect of customer service quality on customer satisfaction at PT Bank Central Asia Tbk, Thamrin branch. The research method used is a survey with questionnaires distributed to customers transacting at the branch. The sample size for this study is 100 respondents, and the data analysis was conducted using SPSS version 2.5. The results indicate that customer service quality has a significant impact on customer satisfaction. The t-test hypothesis shows a significance value of 0.000, which is less than 0.05, with a t-value (20.382) greater than the t-table value (1.984). The coefficient of determination is 0.809, indicating that 80.9% of the variation in customer satisfaction can be explained by customer service quality. The simple linear regression model obtained is Y = 0.205 + 0.950X, indicating that an increase in customer service quality significantly enhances customer satisfaction